2016
DOI: 10.14295/cs.v7i3.1218
|View full text |Cite
|
Sign up to set email alerts
|

Doses e épocas de aplicação de potássio no desempenho agronômico do milho no cerrado piauiense

Abstract: Doses e épocas de aplicação de potássio no desempenho agronômico do milho no cerrado piauiense ResumoPor se tratar de uma fronteira agrícola relativamente nova, o cerrado piauiense ainda necessita de informações quanto ao manejo de adubação potássica, uma vez que, ainda não há uma recomendação técnica de adubação para o milho por parte dos órgãos oficiais de pesquisa. AbstractSince the 'Cerrado' area of Piaui State, Brazil is a relatively new agricultural frontier, there is lack of information regarding the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
2
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
3
2
0
4
Order By: Relevance
“…The corn yields in the first crop (2013-14), and the total production of grain at the end of two growing was changed by applying K, being the maximum rate response at 232 kg ha -1 K2O for corn and 252 kg ha -1 of K2O for the accumulated yield. A similar response was reported by Petter et al (2016), but the response was much more restricted, with the maximum yield obtained at a rate of 53 kg ha -1 K2O, where it was lower than this study. The corn crop 2013-14 encountered conditions of low rainfall during development (only 227 mm), when the last significant rain occurred 29 days after sowing, which reduced productivity to 8,190 kg ha -1 , compared to average historical yield of 8,520 kg ha -1 in the last 5 years.…”
Section: Productivitysupporting
confidence: 88%
“…The corn yields in the first crop (2013-14), and the total production of grain at the end of two growing was changed by applying K, being the maximum rate response at 232 kg ha -1 K2O for corn and 252 kg ha -1 of K2O for the accumulated yield. A similar response was reported by Petter et al (2016), but the response was much more restricted, with the maximum yield obtained at a rate of 53 kg ha -1 K2O, where it was lower than this study. The corn crop 2013-14 encountered conditions of low rainfall during development (only 227 mm), when the last significant rain occurred 29 days after sowing, which reduced productivity to 8,190 kg ha -1 , compared to average historical yield of 8,520 kg ha -1 in the last 5 years.…”
Section: Productivitysupporting
confidence: 88%
“…and Petter et al (2016) observed a significant influence of the application times of K at maize plant height, corroborating with the results of this study. However,Rabê lo et al (2013) did not verify differences in height of the plants submitted to the potassic doses applied at different fertilization periods.…”
supporting
confidence: 92%
“…According to the analysis of variance, the K doses in the two fertilization periods (seeding and V5 stadium) significantly affected the length spike diameter, number of rows of grains, number of grains per row, grain weight and kernel moisture content ( Figure 5). Petter et al (2016) in their study, found similar results, in which K doses influenced all productivity variables except for the length of spikes.…”
Section: Productivity -Maizesupporting
confidence: 64%
“…Potassium, out of the three nutrients investigated and discussed, has the fewest number of studies focused on nutritional efficiency. Petter et al (2016) reported a higher agronomic efficiency for grain yield when the K was split into two doses, in which 50% of the recommended dose was administered at sowing and the remaining 50% at 30 days post sowing, with a 29% higher value than the treatment used in this work. After this, the treatment with the total dose being applied at 30 days post sowing.…”
Section: Potassium (K)mentioning
confidence: 82%